2018
DOI: 10.1128/genomea.00580-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Tilapia Lake Virus Isolate Obtained from Nile Tilapia (Oreochromis niloticus)

Abstract: Since its discovery in 2014, tilapia lake virus (TiLV) has emerged as a significant cause of mortality in tilapia cultured in Asia, Africa, and South America. Here, we report the complete genome sequence of a TiLV isolate obtained during a diagnostic investigation of an ongoing mortality event involving Nile tilapia cultured in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The 5= and 3= untranslated regions of the 10 segments of TiLV WVL19031-01A and WVL19054 were not determined. Maximum likelihood phylogenetic analysis performed in MEGA X (8), based on the nucleotide alignment of the TiLV PB1 gene sequences, supported TiLV WVL19031-01A and WVL19054 as each other's closest relatives and members of a previously determined clade of Thai TiLV strains (3,9) (Fig. 1C).…”
mentioning
confidence: 82%
“…The 5= and 3= untranslated regions of the 10 segments of TiLV WVL19031-01A and WVL19054 were not determined. Maximum likelihood phylogenetic analysis performed in MEGA X (8), based on the nucleotide alignment of the TiLV PB1 gene sequences, supported TiLV WVL19031-01A and WVL19054 as each other's closest relatives and members of a previously determined clade of Thai TiLV strains (3,9) (Fig. 1C).…”
mentioning
confidence: 82%
“…All available reference TiLV sequences (full and partial) were downloaded from NCBI GenBank in September 2019. At the time of writing, six complete or near-complete TiLV genomes were publicly available: two from Israel, Til-4-2011 (KU751814-823 [7]) and AD-2016 (KU552131-142); two from Thailand, TV1 (KX631921-936 [20]) and WVL18053-01A (MH319378-387 [31]); one from Ecuador, EC-2012 (MK392372-381 [32]); and one from Peru, F3-4 (MK425010-019 [14]). These were used to construct alignments of the full coding region of each of the ten segments.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Recently, two different groups published the genomic sequences for TiLV (Al-Hussinee et al, 2018;Bacharach, et al, 2016). Al-Hussinee et al, (2018) with other viral proteins with known immunogenic properties could be heterologously expressed in microalgae to evaluate their potential as antigens to be used in an oral vaccination strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence similarity analyses showed that segment 1 codifies for the RNA polymerase enzyme, while the rest of the RNA segments are codifing for hypothetical proteins without similarities to previously reported proteins, and consequently they have unknown functions. Considering that the virus has spread worldwide since its emergence(Al-Hussinee et al, 2018), it is compulsory to establish prevention measures…”
mentioning
confidence: 99%